Perspektif Akuntansi atas Aset Pengetahuan (Knowledge Asset) - Widyaningdyah, Agnes Utari (Widya Mandala Surabaya Catholic University, 2009)
Today’s economies shifted the dynamic business environment into information age where people interact with knowledge. In this new economy, knowledge management and intellectual capital are emerging as the primary source of wealth. Some companies in Europe have already implemented various knowledge measurement techniques and provide it in particular report called knowledge and intellectual capital report. However all of those techniques and reports have limitations and many suffer from a lack practical testing They need to standardize in order to give a better perception for the participant of the organizations. This paper discusses at the nature knowledge, propose alternative methods of knowledge accounting and the prospects and possibilities for knowledge accounting.